Identification of the optimal automotive R&D area in the context of implementing the Follow-the-Sun strategy – empirical study - Serwiński, Marcin (Identyfikacja optymalnego obszaru B+R sektora motoryzacyjnego w kontekście implementacji strategii Follow-the-Sun – badania empiryczne, 2019)
The main objective of the article is to select an optimal R&D area of the automotive sector in the context of the possibility of implementing the Follow-the-Sun (FTS) strategy. Empirical research covers three areas of R&D of this sector, excluding the area of Software Development, which according to current literature is the only one in which the FTS strategy is applied. The research was conducted between January and August 2019. The spatial scope of the research covered six international automotive companies providing R&D services in at least one of the three surveyed areas. Due to the innovativeness of the presented subject matter, the research part of the study was preceded by the necessary information on the FTS strategy itself. Its main objective is to further increase the pace of R&D work by using project teams dispersed in distant time zones and capable of ensuring a 24-hour work cycle without the need to perform it at night
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 7, s. 271-285, s. 286-298